Attitude to the “uyat” phenomenon among the population - Г. Артыкбаева; С. Амитов; М. Кабылова (Хабаршы. Психология және социология сериясы)
The article is devoted to the sociological analysis of the category of "uyat" (shame) in Kazakhstani society, with an emphasis on its role in the formation of cultural and social norms. The article analyzes interdisciplinary studies of the emotion of shame as a complex phenomenon determined by both individual and sociocultural factors. Various theoretical approaches to the study of shame are considered. Particular attention is paid to social theories of shame, including cultural, ritual and structural concepts that emphasize the importance of interaction between the individual, society and norms of behavior.